2011
DOI: 10.1136/bmj.d1250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on atrial fibrillation: collaborative meta-analysis of published and unpublished evidence from randomised controlled trials

Abstract: Objective To examine whether statins can reduce the risk of atrial fibrillation. Design Meta-analysis of published and unpublished results from larger scale statin trials, with comparison of the findings against the published results from smaller scale or shorter duration studies. Data sources Medline, Embase, and Cochrane's CENTRAL up to October 2010. Unpublished data from longer term trials were obtained through contact with investigators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 73 publications
3
85
0
4
Order By: Relevance
“…199 Similarly, the rate of post-operative atrial fibrillation was halved by perioperative statin therapy in some small randomized trials, but not in larger trials that assessed this outcome systematically. 200 Use of statin therapy has also been associated in observational studies with lower rates of several other conditions (e.g. infections, [201][202][203] chronic obstructive lung disease, [204][205][206] and acute respiratory distress syndrome 207 ), but those claims have been reliably refuted by randomized trials of adequate size.…”
Section: Other Beneficial Effects That Have Been Attributed To Statinmentioning
confidence: 99%
“…199 Similarly, the rate of post-operative atrial fibrillation was halved by perioperative statin therapy in some small randomized trials, but not in larger trials that assessed this outcome systematically. 200 Use of statin therapy has also been associated in observational studies with lower rates of several other conditions (e.g. infections, [201][202][203] chronic obstructive lung disease, [204][205][206] and acute respiratory distress syndrome 207 ), but those claims have been reliably refuted by randomized trials of adequate size.…”
Section: Other Beneficial Effects That Have Been Attributed To Statinmentioning
confidence: 99%
“…A more recent meta-analysis of seven hypothesis-generating trials with 3609 patients and 15 hypothesis-testing trials with 68 504 patients showed a 30% reduction in relative risk of AF in the hypothesis-generating trials and no effect in the hypothesis-testing trials. There was no difference in the effects of statins on primary or secondary prevention of AF [45] . Patel et al [46] included 14 trials with 7402 patients in their meta-analysis and showed that statins decreased AF rates by 45%, new-onset AF by 32%, recurrent AF by 57%, recurrent AF after cardioversion by 42%, and postoperative AF by 58%.…”
Section: Meta-analysesmentioning
confidence: 85%
“…Pooled results from six studies, with more than 160,000 patients (four studies with new-onset AF and two with AF in baseline), revealed an overall risk reduction of 35% with statin therapy (95% CI: 0.55-0.77, p < 0.0001), with the benefit being more conspicuous for new-onset AF (RR = 0.59, 95% CI: 0.48-0.73, p = 0.096) than for secondary prevention of AF (RR = 0.70, 95% CI: 0.43-1.14, p = 0.085) (178). Finally a meta-analysis including all large-scale statin trials did not show a significant reduction in atrial fibrillation in the active treatment group (RR = 0.95, 95% CI: 0.88-1.03, p = 0.24), and seven longer-term trials of more intensive versus standard statin regimens also showed no evidence of a reduction in the risk of atrial fibrillation (RR = 1.00, 95% CI: 0.90-1.12, p = 0.99) (129). Taken together, these findings suggest that statin treatment is not effective in the primary prevention of AF; however, it should be noted that AF was either not recorded or not included among the outcomes of the largest statin trials and event information for these analyses was mostly based on routinely collected data on adverse events.…”
Section: Primary Prevention Of Afmentioning
confidence: 95%